Pyelonephritis: What are the present day causative organisms and antibiotic susceptibilities?. Issue 6 (27th May 2013) - Prabhu, Ajay; Taylor, Peter; Konecny, Pam; Brown, Mark A
Abstract Aim Infections of the lower urinary tract and Acute Pyelonephritis are commonly encountered in clinical practice. Widespread usage of antibiotics and changing susceptibility profiles of uropathogens requires regular review of treatment guidelines to meet these challenges. We aimed to better understand the prevalence of uropathogens and emerging antibiotic resistance in patients with pyelonephritis requiring hospital admission. Methods In this single centre, 12‐year retrospective observational study, we reviewed case notes and urine culture results of 249 patients admitted with Acute Pyelonephritis under the care of the Nephrology Department, along with 46 660 urine samples with positive isolates from the Emergency Department (ED) during the same period. The prevalence of uropathogens, their antibiotic susceptibilities and emerging resistance patterns to commonly used antibiotics were studied. Antibiotic susceptibilities were also reviewed in line with the currently recommended national guidelines for empiric therapy. Results We found the most prevalent uropathogen to be Escherichia coli. Approximately 50% of E. coli infections were resistant to ampicillin. First and third generation cephalosporin resistance was <5%, however, the latter has increased over the last decade and is more prevalent in the elderly. Enterococcus faecalis was associated with less than 10% of cases of lower urinary tract infections and no case of pyelonephritis. Conclusion Antibiotic resistance of uropathogens to commonly used antibiotics is increasing with time and there is a need for hospitals to review their recommended guidelines for empiric therapy in line with local patterns of uropathogens and antibiotic susceptibilities.